The impact of types of green packaging and knowledge of packaging on consumers’ purchase intention. - Gumala, Joice Vania. (2012)
This study was a causal research, which intended todetermine the motivation behind consumers’ purchase intention on green products/packaging. Eventually, the main objective is to provide businesses entering the green market with the survey findings of which type of packaging is more popular among consumers and what factors to consider to make their investment in green market paid off. The revised conceptual framework consists of two independent variables; types of packaging and knowledge of packaging which lead to purchase intention as dependent variable. There is also one moderator; clarity of green information, which affects relationship between types of packaging and intention to purchase.